Бўлажак муҳандисларнинг индивидуал таълим траекториясини амалга оширишда мустақил ишларнинг шаклларидан фойдаланиш - Хожиев, А.К (SCIENCE and SOCIETY, 2023)
This article describes the issues of effective use of forms of organizing independent work of future engineers within the individual educational trajectory of future engineers in order to increase the quality indicators of mastering engineering sciences in higher educational institutions, to acquire additional knowledge and skills to ensure
Keywords: student's independent work; individual educational route; educational trajectory; formation of professional skills; professional qualities; forms of independent work